Evaluation of the health effects of the new driving penalty point system in the Lazio Region, Italy, 2001–4. Issue 1 (12th February 2007) - Farchi, Sara; Chini, Francesco; Giorgi Rossi, Paolo; Camilloni, Laura; Borgia, Piero; Guasticchi, Gabriella
Abstract : Objective: The penalty point system was introduced in Italy in June 2003. The aim of this study was to evaluate the health effects of this legislation in the Lazio region. Methods: Poisson models were used to compare emergency department visits, hospitalizations and death between the pre-law and post-law periods (July 2001–June 2003; July 2003–June 2004). Results: The emergency department visit rate ratio (RR) of the two periods was 0.87 (95% confidence interval (CI) 0.86 to 0.88); the corresponding hospital admission RR was 0.87 (95% CI 0.84 to 0.9). The death RR was 0.93 (95% CI 0.82 to 1.05). Conclusion: After the legislation was introduced, there were fewer visits to the emergency department, hospitalizations and death from road traffic injuries. However, the effect was lower than expected, and it decreased over time.